1942
DOI: 10.1001/jama.1942.02830410005002
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Disability of the Shoulder and Arm

Abstract: severe trauma, the physician usually thinks of the joints, bursae, tendons or nerves rather than of the shoulder girdle muscles as the primary source of pain. Thus the customary diagnosis in this type of patient is either arthritis, subacromial bursitis, brachial neuritis or radiculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
2

Year Published

1944
1944
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(41 citation statements)
references
References 15 publications
6
33
2
Order By: Relevance
“…This is in contrast with the pain-spasm-pain model, first formally proposed by Travell et al (1942) suggesting that pain leads to muscle hyperactivity. The results from the above summarized series of studies do not support that the amount of muscle activity is a linear response to the level of reported pain or disability, although a lack of flexion relaxation of the superficial lumbar multifidus was a common feature of both sub-groups.…”
Section: Motor Pattern Driven By Pain Disability?contrasting
confidence: 65%
“…This is in contrast with the pain-spasm-pain model, first formally proposed by Travell et al (1942) suggesting that pain leads to muscle hyperactivity. The results from the above summarized series of studies do not support that the amount of muscle activity is a linear response to the level of reported pain or disability, although a lack of flexion relaxation of the superficial lumbar multifidus was a common feature of both sub-groups.…”
Section: Motor Pattern Driven By Pain Disability?contrasting
confidence: 65%
“…If muscle spasm causes pain, and pain reflexively produces muscle spasm, a self-perpetuating cycle might be established. 32 While this concept is still widely held, controlled studies have shown no significant difference in resting electromyographic activity when painful and nonpainful muscles are compared. 33,34,35 A painful inflamed muscle can actually have lower-than-normal tension.…”
Section: The Vicious Cycle Relating Muscle Spasm and Pain (1940s)mentioning
confidence: 99%
“…Travell et al (1942) described a condition, "idiopathic myalgia" or "painful shoulder syndrome," in which shoulder pain was hypothesized to be due to tender areas within muscles. They found that "the muscle that most often caused pain in the shoulder region and arm was the serratus posterior superior."…”
Section: Clinical Relevancementioning
confidence: 99%